2019
DOI: 10.3174/ajnr.a6047
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Silent MR Angiography for Intracranial Aneurysms Treated with a Flow-Diverter Device

Abstract: BACKGROUND AND PURPOSE:The flow-diverter device has been established as a treatment procedure for large unruptured intracranial aneurysms. The purpose of this study was to compare the usefulness of Silent MR angiography and time-of-flight MRA to assess the parent artery and the embolization state of the aneurysm after a flow-diverter placement. MATERIALS AND METHODS:Seventy-eight large, unruptured internal carotid aneurysms in 78 patients were the subjects of this study. After 6 months of treatment, they under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
2
39
0
1
Order By: Relevance
“…To rate the flow signal in both zTE-and TOF-MRA images, additional DSA imaging was also available and used as a reference. A separate 4-point scale, reported previously (15,27) for similar analysis, was applied also for data analysis. It is defined as: 4= excellent quality, equal to DSA images; 3= good quality, with minimal blurring or artifacts; 2= poor quality, with structures slightly visible and significant blurring; and 1= not visible.…”
Section: Imaging Assessmentmentioning
confidence: 99%
“…To rate the flow signal in both zTE-and TOF-MRA images, additional DSA imaging was also available and used as a reference. A separate 4-point scale, reported previously (15,27) for similar analysis, was applied also for data analysis. It is defined as: 4= excellent quality, equal to DSA images; 3= good quality, with minimal blurring or artifacts; 2= poor quality, with structures slightly visible and significant blurring; and 1= not visible.…”
Section: Imaging Assessmentmentioning
confidence: 99%
“…Our routine MRA follow-up involves the acquisition of contrast MRA images only when noncontrast MRA results are shown to be or are likely to be equivocal. One potential solution for this may be the use of newer techniques that were not available to us, such as “silent MRA”, which allows better assessment of the stent lumen [ 22 ]. Finally, notwithstanding the facts that our study: (1) has a fairly large number of flow-diverted aneurysms treated and followed by a single group of operators and (2) is the largest series to date focusing strictly on MRA follow-up of flow diverters, the number of aneurysms treated with the new Evolve device in the artifact measurement cohort was lowered significantly due to the selection criteria for the relevant measurement.…”
Section: Limitationsmentioning
confidence: 99%
“… 6) Because repeated DSA examinations are invasive for patients, a less invasive imaging modality has been needed. Oishi et al 7) reported the usefulness of silent MRA for intracranial aneurysms treated with the PED. In the present case, the 6-month follow-up silent MRA showed residual blood flow within the aneurysm.…”
Section: Discussionmentioning
confidence: 99%